Children's exposure to vehicular air pollution in the United States: environmental injustices at the intersection of race/ethnicity and language. Issue 3 (3rd July 2021) - Rubio, Ricardo; Grineski, Sara; Collins, Timothy
ABSTRACT: Children's exposure to hazardous air pollutants (HAPs) from vehicular sources negatively affects their development and health. Using an intersectional approach, we examined differences in exposure based on race/ethnicity and language used at children's homes. We linked 2014 HAP data from the Environmental Protection Agency's (EPA) National Air Toxics Assessment with children's sociodemographic data from the Early Childhood Longitudinal Study, Kindergarten Class of 2010–2011. We analyzed residential exposures for 13, 150 US third-grade children (2013–2014) using generalized estimating equations. Results show that Hispanic and Black children faced disproportionately high exposures to vehicular HAPs as compared to White children, and children from non-English-speaking homes (regardless of race/ethnicity) experienced disproportionate exposure when compared to children from English-speaking homes. Among children who did not speak English at home, Black children were significantly more exposed than White children. White, Asian, and Hispanic children from non-English speaking homes faced disproportionate exposures when compared to their counterparts from English-speaking homes; we did not find the same for Black children. Our intersectional approach illuminates how children's multiple identities shaped their differential exposure to vehicular air pollution, and illustrates the importance of considering within-group inequalities and English-language usage when examining distributional environmental injustices.